Karaite chronography of the 16th–19th centuries from the Crimea and the Polish-Lithuanian Commonwealth - Akhiezer, Golda (Karaite Archives, 2013)
This article focuses on a genre of Karaite historical writing of the Crimea and Poland-Lithuania – the chronography of which has never been researched by scholars. The object of this study is to analyze the main characteristics of this chronography. This genre existed in the Crimea in the 16th-19th centuries and supposedly emerged due to the influence of both Tatar chronicles and Rabbanite historiography. The scanty number of Polish-Lithuanian chronicles from the 17th century on were supposedly affected by Polish chronicles and by Crimean Karaite chronicles. This genre includes a diversity of writings with different characteristics. In order to define them as historical writings I sorted them and divided them into sub-genres. This division, as well as the authors’ purpose in their writings, help us to define whether a certain text is associated with the historical writing and to come to some conclusions about the author’s views concerning history, his self-identification and his mentality in general.